MicroRNAs 155‐5p, 122‐5p, and 181a‐5p Identify Patients With Graft Dysfunction Due to T Cell–Mediated Rejection After Liver Transplantation. Issue 10 (2nd September 2020) - Ruiz, Pablo; Millán, Olga; Ríos, Jose; Díaz, Alba; Sastre, Lydia; Colmenero, Jordi; Crespo, Gonzalo; Brunet, Mercè; Navasa, Miquel
Abstract : MicroRNAs (miRNAs) are small noncoding RNAs that can be detected in plasma and whose expression is associated with pathological processes. The role of miRNAs in the noninvasive diagnosis of T cell–mediated rejection (TCMR) after liver transplantation (LT) is unclear. Thus, we aimed to assess the effectiveness of a panel of 4 miRNAs (155‐5p, 122‐5p, 181a‐5p, and 148‐3p) in diagnosing TCMR in LT recipients with graft dysfunction (GD), and we compared its accuracy with previously published tests for diagnosing TCMR based on routine laboratory parameters. From a prospective cohort of 145 patients followed during the first year after transplant, 49 developed GD and underwent a liver biopsy and plasma collection for miRNA analysis using quantitative real‐time polymerase chain reaction. Patients with GD due to TCMR (n = 21) exhibited significantly higher ( P  < 0.001) expression of miRNA 155‐5p (2.05 versus 0.07), 122‐5p (19.36 versus 1.66), and 181a‐5p (1.33 versus 0.37) compared with those with GD from other causes (n = 28). The area under the receiver operating characteristic curve of miRNAs 155‐5p, 122‐5p, and 181a‐5p for the diagnosis of TCMR was 0.87, 0.91, and 0.89, respectively, significantly higher than those of the other noninvasive tests ( P  < 0.001). Furthermore, miRNA 155‐5p identified all patients who presented TCMR during the first 2 weeks after transplant. miRNA plasmatic expression differentiates TCMR from other causes of GD in patients who have undergone LT and may be a useful tool in clinical practice.